Distorted assessment of left atrial size by echocardiography in patients with increased aortic root diameter - Kaplan, Abdullah; Altara, Raffaele; Manca, Marco; Güneş, Hacı Murat; Cataliotti, Alessandro; Booz, George W.; Zouein, Fouad A. (Springer, 2021)
Background: Left atrial (LA) size is frequently assessed by posterior-anterior linear measurement of LA (LAD P-A) in the parasternal long axis to expedite examination. Aging, changes in body surface area, and several cardiovascular pathologies can affect aortic root (AoR) size, thereby affecting LA anatomical shape. We hypothesized that AoR dilatation influences LAD P-A and consequently correct assessment of LA size. Results: We tested our hypothesis in a study of 70 patients with AoR diameter ranging from 2.7 to 4.8 cm. LA size assessed in parasternal long axis view as LAD P-A was compared to that with LA width and length acquired in the apical two and four chamber view. Simpson's method of discs was used as standard measurement to assess LA volume. We observed that LAD P-A in the parasternal long axis decreases when AoR diameter increases. Thus, the increase in LA size assessed in parasternal long axis did not correlate with the increase of LA volume. Further analysis revealed that a significant positive correlation was observed when LAV was plotted as a function of LAD P-A only for those with a normal size AoR. In contrast, LA volume increase correlated with LA diameters assessed in the apical two and four chamber view regardless of AoR size. Conclusions: Our study documents that increases in AoR impact on the linear measurement of LA, resulting in an underestimated LAD P-A. LA size ought to be calculated from the apical two and four chambers view parameters, especially in patients with AoR dilatation.
Keywords: Echocardiography; Aortic Root Dilation; Left Atrial Structure; Linear Measurement of Left Atrium; Left Atrial Volume